Fikih Kontemporer Dalam Dakwah Gus Baha di Media Sosial - Jamal, Syukron (Indonesia, 2024)
This study aims to analyze how Gus Baha's popularity on the YouTube social media platform, the contemporary fiqh istinbat (legal derivation) methods he applies, and his digital preaching characteristics influence public acceptance of Islamic preaching in the digital era. The research employs a qualitative approach using discourse analysis to explore primary data from Gus Baha’s sermons uploaded on YouTube and secondary data from related academic literature. The analysis is conducted to understand the application of contemporary fiqh istinbat methods in Gus Baha’s sermons and their impact on audience reception. The findings indicate that Gus Baha's popularity on YouTube is highly significant, with the keyword "gus baha terbaru" (latest Gus Baha) reaching a search volume of 72,464 per month, reflecting strong public enthusiasm for his content. This popularity is bolstered by his simple, flexible, humorous delivery style and his relevance to contemporary issues such as the Covid-19 pandemic. The istinbat methods employed by Gus Baha emphasize consistency between traditional principles of Islamic law and modern context relevance. This approach prioritizes maslahat (public benefit) and maqashid syariah (the higher objectives of Islamic law), making his sermons widely accepted across diverse societal groups. Gus Baha’s innovative and adaptive digital preaching characteristics, including the integration of scholarly values, Islamic spirituality, and local wisdom, establish him as a significant figure in addressing the challenges of digital-era preaching. His sermons are not only theologically relevant but also contextual, offering practical solutions to the challenges of modern life. This research underscores that technology-based preaching approaches, such as those employed by Gus Baha, not only enhance accessibility but also strengthen public acceptance of Islamic values.